Risk and solvency regulation of depository institutions / past policies and current options (New York New York university, 1988)
This paper reviews the basis on which public policy toward banks has been constructed in the United state. It further reveals some of the ongoing policies as it affects the banking systems.
include references
asm; 14/02/19
Loans
Keywords: Financial institutions; United State